Cross-Border Disaster Preparedness in the Himalayas by Indian Armed Forces - Shripriya (International Journal of Pollution: Prevention & Control, 2025)
The Himalayan region, known for its immense ecological and geopolitical significance, is also one of the most disaster-prone areas in the world. Its young and dynamic geological structure, coupled with increasing human activity, has amplified the frequency and severity of natural disasters such as landslides, floods, and earthquakes. Cross-border disaster preparedness in the Himalayas, particularly by the Indian Armed Forces, has emerged as a critical component of regional stability and humanitarian assistance. This study examines the physiographic and geodynamic vulnerabilities of the Himalayan region and highlights the proactive role played by the Indian Armed Forces in collaboration with neighboring countries like Nepal and Bhutan. The research emphasizes the importance of regional cooperation, shared resources, and cross-border early warning systems in mitigating disaster risks. Drawing from case studies such as Operation Maitri and Operation Rahat, it underscores the need for dedicated Himalayan-focused disaster management units and regular joint exercises for preparedness and resilience building. Furthermore, the paper explores the integration of advanced technologies like satellite imaging and real-time data sharing for predictive disaster management. It also stresses the significance of empowering local communities through capacity-building initiatives, ensuring that disaster responses are both inclusive and sustainable. The study proposes actionable recommendations, including the establishment of a dedicated Himalayan Guard, advanced training for civil-military coordination, and leveraging regional organizations for effective risk reduction and management. By fostering robust cross-border collaborations and harnessing technological advancements, this paper advocates for a holistic approach to safeguarding the fragile Himalayan ecosystem and its surrounding populations from the escalating challenges of natural disasters.
Keywords: Cross-border disaster preparedness; Disaster Risk Reduction; Himalayan region vulnerabilities; Indian armed forces; regional cooperation